Caspase-dependent apoptosis induces reactivation and gliogenesis of astrocytes in adult mice - Kim, Seung-Chan; Park, Jae-Yong; Hwang, Eun Mi (Frontiers in Cellular Neuroscience, 2022)
Astrocytes play an important role in increasing synaptic plasticity, regulating endogenous homeostasis, and contributing to neuroprotection but become overactivated or apoptotic in persistent neuroinflammatory responses or pathological conditions. Although gliogenesis under these conditions may be essential for neuronal protection, much remains unknown. Here, we generated new conditional transgenic mice (cTg) that can induce apoptosis via Cre-dependent active caspase-3 (taCasp3-2A-TEVp) without pathological conditions. We induced apoptosis of hippocampal CA1 astrocytes in cTg mice using GFAP promoter-driven adeno-associated virus (AAV) containing Cre recombinase. Activated caspase-3 was detected in astrocytes of the hippocampal CA1, and the number of astrocytes decreased sharply at 1 week but recovered at 2 weeks and was maintained until 4 weeks. Nuclear factor 1A (NF1A) mRNA, an important transcription factor for hippocampal reactive astrocytes, was significantly increased only at week 1. Interestingly, all reactive markers (pan, A1, A2) increased despite the decreased number of astrocytes at week 1, and there was no change in monoamine oxidase B (MAOB) observed in astrocytes of animal models of degenerative brain disease. Extensive CA1 astrocyte depletion at week 1 induced cognitive deficits; however, both recovered at weeks 2 and 4. Overall, transient hippocampal astrocyte depletion caused by apoptosis restored cell number and function within 2 weeks and did not induce significant neurotoxicity. Therefore, cTg mice are valuable as an in vivo animal model for studying gliogenesis in multiple regions of the adult brain.